Use of recycled crushed concrete and Secudrain in capillary barriers for slope stabilization - Rahardjo, Harianto (2013)
A capillary barrier is a two-layer cover system having distinct hydraulic properties to minimize water infiltration into the underlying soil by utilizing unsaturated soil mechanics principles. In this study, a capillary barrier system was designed as a cover system for a residual soil slope to maintain stability of the slope by minimizing infiltration during heavy rainfalls in the tropics. The capillary barrier system (CBS) was constructed using fine sand as the fine-grained layer and recycled crushed concrete aggregates as the coarse-grained layer. The coarse-grained layer is commonly constructed using gravels or granite chips. However, due to scarcity of aggregates and in consideration of environmental sustainability, recycled crushed concrete aggregates were used as the coarse-grained layer in this project. The suitability of recycled crushed concrete aggregates as a material within the coarse-grained layer of a CBS is subject to the hydraulic property requirement. For comparison, another CBS was constructed using fine sand as the fine-grained layer and a geosynthetic (Secudrain) as the coarse-grained layer. The performance of each constructed CBS on the residual soil slope was monitored using tensiometers installed at different depths — from 0.6 to 1.8 m below the slope surface — and a rainfall gauge mounted on the slope. An adjacent original slope without the CBS was also instrumented using tensiometers and piezometers to investigate the performance and effectiveness of the CBS in reducing rainwater infiltration and maintaining negative pore-water pressures in the slope. Real-time monitoring systems were developed to examine pore-water pressure, rainfall, and groundwater level in the slopes over a 1 year period. Characteristics of pore-water pressure distributions in the residual soil slope under a CBS with recycled crushed concrete aggregates and in the original slope during typical rainfalls are highlighted and compared. The measurement results show that the CBS was effective in minimizing rainwater infiltration and therefore, maintaining stability of the slope.